Structural-Functional Analysis and Response Surface Methodology (RSM) Modelling of Chitosan-Botanical Extract Edible Coatings and Films - Saputra, Edo; Hasbullah, Rokhani; Darmawati, Emmy; Nurilmala, Mala (Trends in Sciences, 2026)
Demand for bioactive edible coatings and films from renewable biopolymers is increasing due to the need for sustainable alternatives to synthetic plastics. However, achieving formulations that simultaneously optimize mechanical strength, flexibility, and stability of bioactive compounds remains a challenge. This study introduces a novel approach by integrating 3 spice extracts-garlic, red ginger, and red galangal as synergistic reinforcers within a chitosan matrix for edible coating and film systems, modelled through a custom Response Surface Methodology (RSM) design. This study aims to investigate interactive effects between chitosan concentration, extract proportion, and glycerol plasticization on structural performance and bioactive functionality. Fresh extracts of garlic, red ginger, and red galangal were prepared without solvents and combined with chitosan solutions at varying concentrations. Formulations for films included glycerol as a plasticizer, whereas coating formulations excluded glycerol. Results demonstrated that variations in chitosan and extract concentrations significantly influenced pH, antimicrobial activity, tensile strength, and elongation. FTIR analysis confirmed enhanced hydrogen bonding and matrix reinforcement through phenolic-based interactions, explaining improved flexibility and mechanical stability. Conversely, antioxidant activity and inhibition against S. aureus showed non-significant differences across formulations, indicating different sensitivity mechanisms. The RSM model produced highly valid predictive equations for linear, quadratic, and 2FI interaction responses, with strong goodness of fit parameters. The optimal formulation, consisting of 1.33% chitosan and 33.3% extract, generated a balanced performance indicated by pH 4.31, IC₅₀ 4.43 ppm, inhibition zones against E. coli 2.32 mm, S. aureus 4.70 mm, Salmonella 5.23 mm, thickness 0.18 mm, tensile strength 5.01 MPa, elongation 6.00%, and WVTR 252.74 g·day⁻¹·m⁻². These findings provide strong evidence that combining multiple spice extracts within a chitosan matrix improves antimicrobial strength and mechanical flexibility without compromising stability. This study establishes an innovative formulation strategy with significant potential for scalable production of sustainable edible coatings and films as eco-friendly packaging materials. HIGHLIGHTS Chitosan-extract-based coatings and edible films are well formulated and proven to affect pH and inhibit the growth of E. coli and Salmonella. The formulation of chitosan, extract, and glycerol affects the thickness, tensile strength, elongation, and WVTR of edible films. Chitosan extract expands the inhibition zone, lowers IC50, increases thickness, lowers WVTR, but reduces tensile strength; glycerol increases elongation and flexibility. FTIR analysis confirms hydrogen bonding and the contribution of stable active compounds in the coating matrix. Custom RSM modelling produces accurate linear, quadratic, and 2FI models that predict responses, confirming the potential of edible coatings and chitosan-extract films as environmentally friendly food packaging. GRAPHICAL ABSTRACT